2013
DOI: 10.1111/acer.12130
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Behavioral Variability in Cannabinoid Receptor Expression in Outbred Mice Submitted to Ethanol-Induced Locomotor Sensitization Paradigm

Abstract: There are different patterns of cannabinoid receptor expression during locomotor sensitization paradigm, at both temporal and behavioral perspectives. We hypothesize that CB2R down-regulation might be related to resilience to develop locomotor sensitization, while CB1R up-regulation relates to withdrawal aspects in sensitized mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 44 publications
2
18
0
Order By: Relevance
“…Another study found that withdrawal from CIE increased CB 1 transcript in the rat prefrontal cortex (Rimondini et al, 2002). Other work suggests that withdrawal from CIE causes increased CB 1 protein in the hippocampus (Mitrirattanakul et al, 2007; Ceccarini et al, 2013; Coelhoso et al, 2013), striatum (Ceccarini et al, 2013; Coelhoso et al, 2013), and NAc (Coelhoso et al, 2013) that persist for up to 40 days. These results suggest that persistent upregulation of CB 1 occurs during acute withdrawal and protracted abstinence.…”
Section: Effects Of Chronic Ethanol On Cb1 Couplingmentioning
confidence: 99%
“…Another study found that withdrawal from CIE increased CB 1 transcript in the rat prefrontal cortex (Rimondini et al, 2002). Other work suggests that withdrawal from CIE causes increased CB 1 protein in the hippocampus (Mitrirattanakul et al, 2007; Ceccarini et al, 2013; Coelhoso et al, 2013), striatum (Ceccarini et al, 2013; Coelhoso et al, 2013), and NAc (Coelhoso et al, 2013) that persist for up to 40 days. These results suggest that persistent upregulation of CB 1 occurs during acute withdrawal and protracted abstinence.…”
Section: Effects Of Chronic Ethanol On Cb1 Couplingmentioning
confidence: 99%
“…During EtOH‐induced behavioral sensitization (EIBS) paradigm in mice, one robust result is the variability in the rodent's response, with some animals being sensitized at the end of the procedure and others not showing sensitization (called resistant). Although most of the literature on EtOH‐induced behavioral sensitization was dedicated to the mesolimbic circuitry, it has been shown that the dorsal hippocampus may endure some changes after EtOH‐ or other drugs of abuse‐induced sensitization (Degoulet et al, ; Botia et al, ; Coelhoso et al, ; Soares‐Simi et al, ; Legastelois et al, ; Nona et al, ). Different targets have been identified, such as the transcription factor CREB (Soares‐Simi et al, ; Nona et al, ), cannabinoid receptor expression (Coelhoso et al, ), low level of chromatin remodeling (Botia et al, ), BDNF and trkB receptor mRNA expression (Nona et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Although most of the literature on EtOH‐induced behavioral sensitization was dedicated to the mesolimbic circuitry, it has been shown that the dorsal hippocampus may endure some changes after EtOH‐ or other drugs of abuse‐induced sensitization (Degoulet et al, ; Botia et al, ; Coelhoso et al, ; Soares‐Simi et al, ; Legastelois et al, ; Nona et al, ). Different targets have been identified, such as the transcription factor CREB (Soares‐Simi et al, ; Nona et al, ), cannabinoid receptor expression (Coelhoso et al, ), low level of chromatin remodeling (Botia et al, ), BDNF and trkB receptor mRNA expression (Nona et al, ). It is known that drugs of abuse alter NMDA‐dependent bidirectional synaptic plasticity, i.e., long‐term synaptic depression (LTD) and long‐term potentiation (LTP) in the mesolimbic circuit (Lüscher and Malenka, ) and in particular in the nucleus accumbens (NAc) where NMDA receptor‐dependent LTD is abolished by different drugs of abuse (Kasanetz et al, ; Abrahao et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a prolonged withdrawal period after sensitization development is necessary for the establishment of neuroadaptations underlying long-term maintenance of the behavioral response (Vanderschuren and Kalivas, 2000). Such neuroadaptations are related to various neurobiological systems including dopaminergic (Heidbreder et al, 1996), GABAergic (Zhang et al, 2006), glutamatergic (Boudreau and Wolf, 2005), cannabinoidergic (Coelhoso et al, 2013), and opioidergic (Magendzo and Bustos, 2003). More specifically, inhibition of GABA transmission in the NAc persists 28 days after locomotor sensitization to methamphetamine (Zhang et al, 2006), suggesting a long-term disruption of this system after chronic treatment to drug of abuse.…”
Section: Discussionmentioning
confidence: 99%
“…To do so, we took advantage of the high level of individual variability in response to both EIBS (Botia et al, 2012;Legastelois et al, 2014) and anxiety tests (Bahi, 2013;Correia et al, 2009) in mice. Interestingly, we and others reported that significant signs of sensitization following chronic EtOH injections are only observed in a subset of mice, allowing the distinction between sensitized and resistant (nonsensitized) animals (Abrahao et al, 2012;Botia et al, 2012;Coelhoso et al, 2013).…”
mentioning
confidence: 88%